Categorización étnica, conflicto armado interno y reparaciones simbólicas en el Perú post - Comisión de la Verdad y Reconciliación (CVR) - Valérie Robin Azevedo; Dorothée Delacroix (Nuevo mundo - Mundos Nuevos, 2017)
This article questions the key role of the Peruvian Truth and Reconciliation Commission (CVR) in the return of the "indigenous" category, again in use in the national public arena of the 21st century. We analyze its influence on the reparations policies and their repercussions on the forms of identification of the Andean populations. The analysis of the content of the final report of the CVR and the activities carried out in the memorial El Ojo que Llora in Lima highlights the process of ethnicizing the category of victim, as innocent and indigenous. The staging of this positive figure of the Indian sought to counteract the stigma associated with the "Indian", considered a terrorist during the war. However, this position does not fail to convey some essentialism about the inner otherness. In their eagerness to visualize and value Andean cultural elements, don’t human rights activists run the risk of reproducing the exoticism associated with the populations most affected by the war; stigma they denounce in their fight against racism? Similarly, linking contemporary peasant communities with pre-Hispanic past reduces the possibility of fully recognizing this rural population as dynamic actors with their own political subjectivity. Directing the focus to the replica of the Lima memorial in an Andean peasant community allows us to also glimpse how the relations between center and periphery are redefined, through local construction of the collective memory of the internal armed conflict.